Integration of Energy Harvester for Self-Powered Wireless Sensor Network Nodes - Lijuan Chen; Xiaohui Xu; Pingliang Zeng; Jianqiang Ma (International Journal of Distributed Sensor Networks)
This paper reports an energy harvester suitable for self-powered wireless sensor network (WSN) nodes consisting of a piezoelectric cantilever, an energy harvesting circuit, and a storage capacitor. Having the same size as a credit card, the proposed WSN nodes can be easily integrated into various applications, such as motor and air conditioning equipment. The WSN node is powered by an integrated bimorph piezoelectric generator that harvests energy from ambient vibration. The paper has developed a method to optimize the harvester parameters to attune it to the dominant vibration frequency. Tests carried out on the proposed harvester show that the proposed design can meet the energy requirements of a WSN node and achieve an efficiency of 79%.